Respuesta :

Answer:

[tex]y(2)=2e^{2\tan^{-1}(2)}[/tex]

Step-by-step explanation:

Given the initial value problem.

[tex]\frac{dy}{dx}=\frac{2y}{1+x^2} ; \ y(0)=2[/tex]

Find y(2)

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

[tex]\boxed{\left\begin{array}{ccc}\text{\underline{Seperable Differential Equation:}}\\\frac{dy}{dx} =f(x)g(y)\\\\\rightarrow\int\frac{dy}{g(y)}=\int f(x)dx \end{array}\right }[/tex]

(1) - Solving the separable DE

[tex]\frac{dy}{dx}=\frac{2y}{1+x^2} \\\\\Longrightarrow \frac{1}{y}dy =\frac{2}{1+x^2}dx\\ \\\Longrightarrow \int \frac{1}{y}dy =2 \int\frac{1}{1+x^2}dx\\\\\Longrightarrow \boxed{ \ln(y)=2\tan^{-1}(x)+C}[/tex]

(2) - Find the arbitrary constant "C" with the initial condition

[tex]\text{Recall} \rightarrow y(0)=2\\ \\ \ln(y)=2\tan^{-1}(x)+C\\\\\Longrightarrow \ln(2)=2\tan^{-1}(0)+C\\\\\Longrightarrow \ln(2)=0+C\\\\\therefore \boxed{C=\ln(2)}[/tex]

(3) - Form the solution

[tex]\boxed{\boxed{ \ln(y)=2\tan^{-1}(x)+\ln(2)}}[/tex]

(4) - Solve for y

[tex]\ln(y)=2\tan^{-1}(x)+\ln(2)\\\\ \Longrightarrow \ln(y)-\ln(2)=2\tan^{-1}(x)\\\\ \Longrightarrow \ln(\frac{y}{2} )=2\tan^{-1}(x)\\\\ \Longrightarrow e^{\ln(\frac{y}{2} )}=e^{2\tan^{-1}(x)}\\\\ \Longrightarrow \frac{y}{2} =e^{2\tan^{-1}(x)}\\\\\therefore \boxed{y=2e^{2\tan^{-1}(x)}}[/tex]

(5) - Find y(2)

[tex]y=2e^{2\tan^{-1}(x)}\\\\\therefore \boxed{\boxed{y(2)=2e^{2\tan^{-1}(2)}}}[/tex]

Thus, the problem is solved.

ACCESS MORE